IMAM SALAT PEREMPUAN BAGI LAKI-LAKI - Tobibatussaadah, Tobibatussaadah (P3M STAIN Jurai Siwo Metro, 2011)
AbstractSome Hadith shows that women should be priests to other women as it is commonly done by several wives apostle of Allah. About women becoming priests pray for the men there were traditions that indicate that the women should be priests pray for the families at home. While women become priests prayed for men who are not members of the family, no tradition is expressly prohibited. There are only traditions that forbid a priest in the Friday prayers. This research is interesting because it relates to the function and role of women in the realm of worship. This research was conducted by the research method approach Hadith yan done with a model approach to historical research. This is because the text books of hadith is one of the studied historical documents. The study was conducted simultaneously with critiquing the quality of tradition based on information from the books of Hadith rijalul assembly. Based on research, that the hadith that forbids women to the priesthood Prayer Hadith daeef status. In addition, these traditions with respect to Friday prayers. While the Friday prayers for women are not required. While the tradition of female imams pray for men, bersetatus hasan lighairihi. Context of tradition, women become priests pray for these men in the area of domestic or family environment. As for the public there is no hadith that prohibits or who ordered it. In the context of the terminology of usul in fact permissible under the law.Â Keywords: Hadits, Imam dan Perempuan